Thoughts that fatten. "Thought - form" fusion in eating disorders - Starzomska, Małgorzata; Brytek - Matera, Anna (Studia Psychologica: Theoria et praxis, 2012)
Psychiatric disorders are characterized by a range of specific cognitive distortions. One of the most interesting cognitive phenomena is Thought-Shape Fusion, which occurs when thinking about eating certain types of food increases a person’s estimate of their shape and/or weight, elicits a perception of moral wrongdoing, and/or makes the person feel fat. TSF can be induced experimentally in healthy volunteers, but it is especially associated with eating pathology. It may be that thought–shape fusion is both a direct expression of the core psychopathology and also serves to maintain it. In patients for whom thought–shape fusion appears